Voix de revenants dans les Pièces pour danseurs de W.B. Yeats. L’exemple de Ce que rêvent les os - Pierre Longuenesse (Conserveries Mémorielles)
In The Dreaming of the Bones, written after the turmoil of the 1916 Easter Rising, Yeats presents, following the Noh tradition model, a young rebel fugitive confronted by two ghosts, caught half-way between past and present, dream and reality. The figure of the past coming to haunt the present thus plays as pivotal a role in the fable as the form in which the writing unfolds. On the one hand, everything in the play is a return, as the events of the Easter Rising re-enact, from the other end of historical time, the event which gave rise to the oppression resulting from the betrayal of the royal couple, Diarmuid and Devorgilla when, dispossessed of their kingdom, they sought the assistance of the Anglo-Normans to reclaim it. On the other hand, through a subtle relationship between the visual and aural, and the new form taken by speech and enunciation, it is the role of the voice, according to defined protocols, to express this presence-absence and this drama of an impossible return. This type of spectral projection is furthermore intensified by the fact that the “theatrical representation” is only conveyed to us through the eyes – or possibly dreams – of a group of musicians, without any stage direction, which might situate this visual and aural universe in a given system of reference. The action that unfolds before the spectator thus becomes a projection of his imaginary landscape, the “music of the lost kingdom” of memory, brought forth by the power of utterance. In this manner the writing itself becomes the place where dreams can emerge through its capacity to conjure up things that are simultaneously shown to be absent. The play is merely a poetic variation on the question “Who’s there ?”.